Consumers' adoption of parcel locker service: protection and technology perspectives - Hyun Sang An; Arim Park; Ju Myung Song; Christina Chung (Cogent Business & Management, 2022)
This study examines consumers' decision to select parcel locker service with regard to privacy concerns and perceptions toward technology based on protection motivation theory and the technology acceptance model. A total of 310 consumers using online shopping and delivery services in the 10 most populated metropolitan areas in the United States were recruited. The responses in the final sample were analyzed by using Structural Equation Modeling (SEM). The findings of this study show that consumers' perceived trust in technology-based service (rather than privacy concerns) more strongly evoke parcel locker service adoption intention in consumers' sequential decision-making process, which encompasses threat/coping appraisal, protection motivation, perceived innovativeness from a new service, service trust, perceived usefulness, perceived ease of use, and attitude toward the new service-outdoor parcel locker service. This study provides managerial implications for retailers who need to deliver packages to consumers. This study attempts to understand consumers' decision-making process toward adopting parcel locker service by considering two approaches: technology assessment and privacy protection.
Keywords: 650; technology acceptance model; consumer decision-making; parcel locker; protection motivation theory